"Accompagner" des sujets malades en appartement de coordination thérapeutique : regards croisés des professionnels - Martha Isabel Arciniegas Cardoso (Éducation et Socialisation)
This article arises from a collaborative research-action led within an association which welcomes of elderly between 18 and 60 years, living with one or several invalidating chronic diseases being in a precarious situation. This association proposes an accommodation and a global support by means of a plan named -apartment of therapeutic coordination-. This support is implemented by a multidisciplinary team. The objective of this contribution is on one hand to report what recovers the notion of accompaniment for the professionals who accompany the welcomed sick people and on the other hand, to analyse how this support is lived, thought, and acted by these practitioners. The professionals experience ‘to accompany’ in the same institution but in a different way. These differences find their genesis in the meanings attributed to the act of accompany giving rise to several figures of the accompaniment and raise the complex question relative to the articulation of various cultures of professional action.